Luminal NaCl delivery regulates basolateral PGE(2) release from macula densa cells - Peti-Peterdi, János (American Society for Clinical Investigation, 2003)
Macula densa (MD) cells express COX-2 and COX-2–derived PGs appear to signal the release of renin from the renal juxtaglomerular apparatus, especially during volume depletion. However, the synthetic machinery and identity of the specific prostanoid released from intact MD cells remains uncertain. In the present studies, a novel biosensor tool was engineered to directly determine whether MD cells release PGE(2) in response to low luminal NaCl concentration ([NaCl](L)). HEK293 cells were transfected with the Ca(2+)-coupled E-prostanoid receptor EP(1) (HEK/EP(1)) and loaded with fura-2. HEK/EP(1) cells produced a significant elevation in intracellular [Ca(2+)] ([Ca(2+)](i)) by 29.6 ± 12.8 nM (n = 6) when positioned at the basolateral surface of isolated perfused MD cells and [NaCl](L) was reduced from 150 mM to zero. HEK/EP(1) [Ca(2+)](i) responses were observed mainly in preparations from rabbits on a low-salt diet and were completely inhibited by either a selective COX-2 inhibitor or an EP(1) antagonist, and also by 100 μM luminal furosemide. Also, 20-mM graduated reductions in [NaCl](L) between 80 and 0 mM caused step-by-step increases in HEK/EP(1) [Ca(2+)](i). Low-salt diet greatly increased the expression of both COX-2 and microsome-associated PGE synthase (mPGES) in the MD. These studies provide the first direct evidence that intact MD cells synthesize and release PGE(2) during reduced luminal salt content and suggest that this response is important in the control of renin release and renal vascular resistance during salt deprivation.